A complex social-ecological disaster: Environmentally induced forced migration. Issue 4 (1st October 2016) - Rechkemmer, Andreas; O'Connor, Ashley; Rai, Abha; Decker Sparks, Jessica L.; Mudliar, Pranietha; Shultz, James M.
ABSTRACT: In the 21 st century, global issues are increasingly characterized by inter-connectedness and complexity. Global environmental change, and climate change in particular, has become a powerful driver and catalyst of forced migration and internal displacement of people. Environmental migrants may far outnumber any other group of displaced people and refugees in the years to come. Deeper scientific integration, especially across the social sciences, is a prerequisite to tackle this issue.